Análise da relação entre preço e lucro num ambiente de convergência às normas internacionais : uma abordagem com equações simultâneas - Potin, Samuel (2016)
Especially from the 60's the relationship between price and earnings has been studied in more depth in order to understand the importance of accounting numbers for the market and how this relationship occurs. Essentially with Law 11.638/07 Brazil is engaged in the process of harmonization of national accounting standards with international standards (IFRS). It is expected that such harmonization will increase the quality of information from accounting reports. Due to this fact, the main objective of this dissertation is to investigate the relationship between price and earnings in a convergence environment to international standards by analyzing the impact of the adoption of full IFRS on the quality of accounting information that this research will be analyzed from the perspective of timeliness and the relevance of earnings and equity, using for this a model of simultaneous equations and partial correlations and semi-partial. For the execution of this work were formed two samples with non-financial companies listed on São Paulo’s Stock Market. A sample covering the period 2002-2007 (BR GAAP) and another comprising the period 2010-2015 (full IFRS). The final sample for the BR-GAAP period included 345 observations companies-year and full IFRS sample was obtained 710 observations companies-year. Several studies addressing the impact of the adoption of international accounting standards have been made at national and international level, but usually using single equation models, not investigating the simultaneous relationship between the model variables. Paying attention to this question, this research will investigate the first hypothesis the existence of simultaneous relationship between price and earnings; will also investigate the second and third hypotheses price and earnings contain information to explain each other, the fourth and fifth hypotheses testing, respectively the relevance of earnings and timeliness increased after the adoption of full IFRS and, finally, the latter hypothesis tests whether the financial statements in full IFRSs are more relevant than in BR GAAP. The results show that price and earnings are determined simultaneously, and although both price and earnings contain information to explain each other in both accounting standards. Considered together, the accounting information gained importance after the adoption of full IFRS. However when analyzing separately, the results show that the earnings lost relevance, but the equity gained relevance after adoption. The timeliness of financial information increased after the adoption of full IFRS. The results show an additional effect of the adoption of full IFRS, that the share price is simultaneously formed the formation of earnings, so that the share price gains relevance to explain the earnings by increasing the relevance of information that are brought by investors thus, the adoption of international standards helps the market to reflect more timeliness form the information will be disclosed by the companies.